Mobility Limitations and Fall‐Related Factors Contribute to the Reduced Health‐Related Quality of Life in Older Adults With Chronic Musculoskeletal Pain. Issue 1 (3rd December 2014) - Stubbs, Brendon; Schofield, Pat; Patchay, Sandhi
Abstract: Purpose: To investigate (1) the prevalence of chronic musculoskeletal pain (CMP) among a sample of community‐dwelling older adults and (2) health‐related quality of life (HRQOL) in people with CMP, particularly the association with mobility limitations and falls‐related factors. Method: Overall, 295 (response rate 73.5%) community‐dwelling older adults were recruited across 10 sites. CMP was assessed using recognized criteria. In the sample of people with CMP, a hierarchical multiple regression analysis was conducted with HRQOL as the dependent variable and a number of independent variables were then inserted into the model. After controlling for demographic and medical variables, mobility (timed up and go (TUG), walking aid use, sedentary behavior) and fall‐related factors (falls history, balance confidence, concerns about consequences of falling) were inserted into the model at the second step and changes in adjusted R 2 noted. Results: Within our sample of older adults, 52% had CMP (154/295). Compared to the group without CMP of similar age ( n  = 141), those with CMP had reduced HRQOL and profound mobility limitations and more falls risk factors ( P  < 0.001). The mobility and falls explanatory variables increased the variance explained within HRQOL from 14% to 36% (adjusted R 2 change 20%) in those with CMP. Sedentary behavior, pain interference, concerns about the consequences of falling, falls history, TUG scores, and balance confidence all remained significant predictors of HRQOL in the fully adjusted model in the CMP sample. Conclusion: Older adults with CMP have pronounced mobility limitations and increased falls risk factors, and these are associated with a marked reduction in HRQOL. Future prospective research is required to build on this cross‐sectional study.